Historical Analysis of Caliph Uthmān bin ʿAffān’s Policy (Period 24 AH-29 AH) - Assidiqi, Muhammad Raqib; Putra, Grand Colin Amdhana Priin (Yayasan Pesantren Mahasiswa An-Nur, 2024)
This paper provides a detailed analysis of the early period of Uthman bin Affan's caliphate, spanning 24 AH to 29 AH. Utilizing Ibn Khaldun's historical methodology, the study critically examines the policies and events that shaped this crucial period in Islamic history. The research begins with a brief biography of Uthman bin Affan, highlighting his character traits and significant positions before his caliphate. It then delves into the critical policies implemented by the third caliph, including cabinet reshuffles, military expansions, economic reforms, and other administrative measures. The discussion explores the factors influencing these policy decisions, such as the wills of previous caliphs, disputes among companions, and the caliph's ijtihād. The military campaigns that led to the liberation of territories like Azerbaijan, Armenia, Cyprus, and Tunis are examined, along with their economic implications for the Islamic state. The study also sheds light on Uthman bin Affan's economic policies, including distributing war booty, land empowerment, and establishing a police force. Throughout the paper, it is argued that while Uthman bin Affan largely continued the policies of his predecessors, he also made necessary changes and developments in response to the expanding Islamic state. The article concludes by emphasizing the importance of understanding the historical context and factors behind the policy decisions made during this period.